Peranan filsafat dan bahasa sebagai media komunikasi: Filsafat dan bahasa - Rori, Muhammad AS; Subhan, Roni (Kampret Journal, 2024)
This article discusses the role of philosophy of language in the development of linguistics, especially in terms of helping scientists think scientifically. The author explains that language is a tool for drawing inductive and deductive conclusions, as well as for carrying out syllogisms. The author also outlines several branches of language philosophy, such as logic, semantics, pragmatics, and hermeneutics, and their relationship with linguistics. The author emphasizes that the philosophy of language and linguistics interact and influence each other in understanding language phenomena.